Asthma amplifies dementia risk: Evidence from CSF biomarkers and cognitive decline. Issue 1 (8th July 2022) - Nair, Ajay Kumar; Van Hulle, Carol A.; Bendlin, Barbara B.; Zetterberg, Henrik; Blennow, Kaj; Wild, Norbert; Kollmorgen, Gwendlyn; Suridjan, Ivonne; Busse, William W.; Rosenkranz, Melissa A.
Abstract: Introduction: Evidence from epidemiology, neuroimaging, and animal models indicates that asthma adversely affects the brain, but the nature and extent of neuropathophysiological impact remain unclear. Methods: We tested the hypothesis that asthma is a risk factor for dementia by comparing cognitive performance and cerebrospinal fluid biomarkers of glial activation/neuroinflammation, neurodegeneration, and Alzheimer's disease (AD) pathology in 60 participants with asthma to 315 non‐asthma age‐matched control participants (45–93 years), in a sample enriched for AD risk. Results: Participants with severe asthma had higher neurogranin concentrations compared to controls and those with mild asthma. Positive relationships between cardiovascular risk and concentrations of neurogranin and α‐synuclein were amplified in severe asthma. Severe asthma also amplified the deleterious associations that apolipoprotein E ε4 carrier status, cardiovascular risk, and phosphorylated tau181 /amyloid beta42 have with rate of cognitive decline. Discussion: Our data suggest that severe asthma is associated with synaptic degeneration and may compound risk for dementia posed by cardiovascular disease and genetic predisposition. Highlights: Those with severe asthma showed evidence of higher dementia risk than controls evidenced by: higher levels of the synaptic degeneration biomarker neurogranin regardless of cognitive status, cardiovascular or genetic risk, and controlling for demographics. steeper increase in levels of synaptic degeneration biomarkers neurogranin and α‐synuclein with increasing cardiovascular risk. accelerated cognitive decline with higher cardiovascular risk, genetic predisposition, or pathological tau.